Point-of-Care Thromboelastography for Intrathecal Drain Management in Patients With Coagulopathy and Thoracic Aorta Surgery: A Case Report. Issue 12 (15th December 2019) - Bortman, Jeffrey; Chaudhry, Omar; Sharkey, Aidan; Sohail, Mahad; Bose, Ruma; Matyal, Robina
Abstract : Spinal drain placement to prevent spinal cord ischemia during thoracic aorta surgery is a necessary yet complex undertaking in patients with coagulopathies. Thromboelastography (TEG) can be used as a point-of-care management tool to monitor coagulation status before drain placement and removal. We present 2 cases: a case of a patient with factor VII deficiency and a case of a patient with thrombocytopenia for whom TEG was an important procedural adjunct during coagulopathy reversal. TEG parameters are also discussed to encourage more frequent TEG use as an adjunct during these complex cases.